Sustainable Development for Vulnerable poor in Indian economy - Dr. Swati Sanadhy (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
But for him, India would have left much less the winds of change that had been blowing over the world; he made us aware of them and also more receptive. Yet he failed his people insofar as he could not adequately execute the great mandate, he had from them because he just was not relentless enough. He was our beautiful but ineffectual angel, beating his beautiful wings largely in vain.hirendranath Mukherjee (1964). The Gentle Colossus: A study of Inclusive growth achievement path Sustainable development is essential for the growth of modern economy. The present study is a venture to analyse the sectors that can have a positive impact on its development. Sustainable development can be reinforced if a region has a sound economic infrastructure, robust industrial development, demographically developed and water resources, energy and fed individuals. The secondary data gathered from various government publications and research articles has been put to various statistical techniques like ranking, principal component analysis and stepwise regression. The current energy challenges can be met with an integral policy for long term growth diverted to the development of various sector viz.industry, infrastructure, demography, agriculture etc. given the critical role of energy development in improving not only the quality of life but also productivity in various sector, a multipronged strategy have been suggested in the present study to help the planners and policy makers.